Stability Guaranteed and Simulation of Heliostat on Testing-Ground - Bedaouche, Fatah; Hassam, Abdelouahab; Boubezoula, Mabrouk (Elektronika ir Elektrotechnika, 2017)
Recently, the heliostat field attracts great attention by searchers in order to boost the electrical performance and harvest great energy. For efficient use, heliostats are generally installed on open-plated areas. The problem stated in this work consists of how heliostats can benefit on distorted grounds? Accordingly, in this work, the dynamic model of heliostat mechanical structure is developed basing on Lagrange formalism. In addition, the system of the heliostat is realized in virtual reality with a real dimension and a program for calculating the sun position and tracking the sun trajectory is developed. Moreover, to ensure a good tracking of the system in control closed loop the state feedback synthesis with pole placement based on LMI constraints is used and basing on the quasi-LPV modelling to guarantee the stability of heliostat on testing-ground. The obtained results averred the robustness of the proposed control strategy. This study can be taken into consideration in the implementation of central power towers on different ground shapes. DOI: http://dx.doi.org/10.5755/j01.eie.23.5.19246